Rational heterojunction design of 1D WO3 nanorods decorated with vertical 2D MoS2 nanosheets for enhanced photoelectrochemical performance - Seo, Dong Bum; Dongquoc, Viet; Jayarathna, Roshani Awanthika; Lee, Sangyeob; Lee, Jae Hyun; Kim, Eui Tae (Journal of Alloys and Compounds, 2022)
The development of the heterostructures of one-dimensional (1D) and two-dimensional (2D) semiconductors is a prospective strategy to design an efficient photoanode for photoelectrochemical (PEC) water splitting. In this study, we report the controllable growth and beneficial heterojunction effects of vertically-aligned 2D MoS2 nanosheets (NSs) on 1D WO3 nanorods (NRs) for efficient PEC water-splitting reactivity. MoS2 NSs were decorated on WO3 NRs by metal–organic chemical vapor deposition. In comparison with pristine WO3 NRs, vertical MoS2 NSs-decorated WO3 NRs possessed an enlarged surface area, improved light absorption performance, and appropriately organized the staggered heterojunction of MoS2/WO3 for promoting the PEC reaction. PEC performance was considerably affected by the size of vertical MoS2 NSs. MoS2/WO3 structure with appropriate MoS2 NS size showed a 72% enhancement in PEC performance compared with pristine WO3. These results provide a valuable strategy for constructing staggered heterojunctions and introducing morphology control for beneficial PEC applications.
Keywords: Controllable growth; Metal-organic chemical vapour depositions; One-dimensional; Photo-anodes; Photo-electrochemistry; Photoelectrochemical performance; Photoelectrochemical water splitting; Prospectives; Two-dimensional; Vertically aligned; Heterostructures; Molybdenum disulfide; Nanosheets; Nanowires; Photoelectrochemistry; Tungsten oxide